Nika Bačić Selanec, Davor Petrić, Migrating with Dignity: Conceptualising Human Dignity Through EU Migration Law, „European Constitutional Law Review” 2021, vol. 17, iss. 3, pp. 498-516, https://doi.org/10.1017/S1574019621000262 - Narożniak, Agnieszka (Studia Prawa Publicznego, 2022)
Nika Bačić Selanec, Davor Petrić, Migrating with Dignity: Conceptualising Human Dignity Through EU Migration Law (Migrować z godnością: konceptualizacja godności ludzkiej w prawie migracyjnym UE), „European Constitutional Law Review” 2021, vol. 17, iss. 3, pp. 498-516, https://doi.org/10.1017/S1574019621000262